Financial Feasibility Analysis of Coffee Roasting Business (Case Study in Coffee Misconception Shop) - Muhammad Choiril Anam; Muhammad Juwanda; Suci Nur Utami (CV. Rayyan Dwi Bharata, 2023)
The coffee roasting business at the Kelirumologi Kopi shop has a very big opportunity to run because there are no competitors in the Kersana District area. But on the other hand, is this business financially viable or not? Therefore, this study aims to determine the feasibility of financial analysis in coffee roasting businesses in Kelirumology Coffee. The method used in this study is a quantitative method that is used to analyze the calculation of financial aspects such as Payback Period, Net Present Value and Profitability Index. The results of the study show that the calculation results from financial analysis are declared feasible to run because the Payback Period value is smaller than the investment age, namely 1 year 8.7 months with an investment age of 3 years, the NPV is more than 0 and has a positive value of Rp. 65,922,388 and PI is accepted because the calculation results show more than 1, namely 1.8.